PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN DAN KINERJA EKONOMI - Kusmiyatun, Kusmiyatun; Ramdhani, Dadan (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This research aims to examine the influence of corporate social responsibility disclosure and environmental performance to financial performance and economic performance. The sample used in this study is manufaktur companies listed on the Indonesia stock exchange, corporate social responsibility disclosure, participate in PROPER since 2010 until 2015, which are 13 firm. Purposive the sampling was used as sampling method. The results showed the corporate social responsibility disclosure effect to financial performance, environmental performance effect to financial performance and corporate social responsibility disclosure does not effect to financial performance, environmental performance doesnot effect to economic performance.Keyword : corporate social responsibility, environmental performance, financial performance, economic performance